2013
DOI: 10.2478/jee-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Network Reconfiguration Considering Power Losses and Outages Costs Using Genetic Algorithm

Abstract: This paper discusses the problem of finding the optimal network topological configuration by changing the feeder status. The reconfiguration problem is considered as a multiobjective problem aiming to minimize power losses and total interruptions costs subject to the system constraints: the network radiality voltage limits and feeder capability limits. Due to its complexity, the metaheuristic methods can be applied to solve the problem and often the choice is genetic algorithm. NSGA II is used to solve the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…One of them is NSGA II, which belongs to the Pareto‐based optimisation approaches. One of the main advantages of NSGA II, when compared with the original GA, is the ability to preserve population diversity, using the crowding distance approach and therefore achieve uniform distribution of solutions within the Pareto front and overcome the convergence problem . Non‐dominated sorting genetic algorithm II is widely used because it is robust, efficient, and relatively simple.…”
Section: Theoretical Fundamentalsmentioning
confidence: 99%
“…One of them is NSGA II, which belongs to the Pareto‐based optimisation approaches. One of the main advantages of NSGA II, when compared with the original GA, is the ability to preserve population diversity, using the crowding distance approach and therefore achieve uniform distribution of solutions within the Pareto front and overcome the convergence problem . Non‐dominated sorting genetic algorithm II is widely used because it is robust, efficient, and relatively simple.…”
Section: Theoretical Fundamentalsmentioning
confidence: 99%
“…The result obtained showed the possibility of finding optimal state of the switches which will in turn produce smaller total losses and smaller total customer interruption costs. The limitation of the work was that it only encompassed active losses in calculating network losses while other losses like those due to insulation off-lines and capacitors were not accommodated [7] Tomoiaga et al (2013) addressed DFR using GA based on graph theory with a view to minimizing active power losses. Backward/forward sweep load flow techniques were used to determine steady state parameters of the network algorithms.…”
Section: 0mentioning
confidence: 99%
“…This in no doubt affected the fidelity of distribution system in faithfully delivering the energy meant for sale to customers.Ideally, distribution network is expected to supply electrical power to all connected customers in a manner to avoid overloading, feeder thermal overload and abnormal voltage across the line, as well as minimization of active power loss andmaintenance of radial topologysimultaneously [4]. Previous researches had shown that the reverse is the case, it was estimated thatout of totally generated electrical power, 13% of powerloss occurs at distribution system alone [3,[5][6] which is a wide margin deviation from permissible power loss of 3-6 % in an ideal RDS [7]. Researcher [8] identified the major problems of radial distribution network (RDN) to include low reliability, low voltage and high-power loss.…”
Section: Introductionmentioning
confidence: 99%
“…DSR is the act of opening and closing the switching devices of power systems to reach a topology that optimizes the desired objectives [1]. Variety of objectives such as power losses and total interruptions [2], Load Balancing [3], Voltage Profile Improvement [4], Service Restoration [5], reliability and power quality improvement [6] has been considered to solve DSR problem. A rigorous classification of the DSR solution methods is difficult.…”
Section: Introductionmentioning
confidence: 99%